Stres Kerja dengan Kinerja Perawat - I Gede Widjanegara; I Gusti Ayu Harini (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2013)
This research aim to know the relationship between stress of work with performance of nurse in RSUD Sanjiwani Gianyar year 2011. This research used descriptive research with crossectional approach use the instrument of stress of work scale and BARS. The result of stress of work showed as 19,6% respondents have high stress of work, 73,2% respondent have middle stress of work, and 7,2% have lower stress of work. The result of performance showed as 28,6% respondent have good performance, 57,1% respondent have middle performance, and 14,3% respondent have lower performance. Statistic rank spearman correlation test has very significant result between stress of work with performance and the correlation is negative